The case for a meta‐nosological investigation of pragmatic disease definition and classification - Livingstone-Banks, J (Wiley, 2018)
Nosology is the science of defining and classifying diseases. Meta‐nosology is the study of how we do this, on what principles nosological practices are based, the quality of the resulting medical taxonomy, and primarily whether/how diseases can be defined better than they are now. In modern Western medicine, there are a wide variety of ways in which diseases are defined and categorized. Examples include by the symptoms they present with (syndromic), their underlying causes (etiological), the biological mechanisms involved (pathogenetic), available treatments, historical precedent, and through diagnostic exclusion. Here, I explore the hypothesis that how we define diseases has an impact on how (and how effectively) we research and treat them. I explore the philosophical implications of this thesis and suggest a direction that the underlying metaphysics of disease definition might follow. I conclude that further research is warranted into whether our current disease definitions could be improved upon.